Modelling Sensitivity of Stream flow to Climate Change in the Brahmani River Basin - Islam, Adlul; Sikka, Alok K; Saha, B; Anamika, Anamika (Journal of Agricultural Engineering, 2009)
It is widely accepted that increasing concentration of greenhouse gases in the atmosphere is causing climate change, which may alter the hydrologic cycle and regional water availability. Hydrological modelling to assess the sensitivity of stream flow in the Brahmani basin to different hypothetical climate change scenarios indicated significant changes in mean monthly stream flow. Simulation results indicated 76% increase in annual stream flow with a 30% increase in rainfall and no change in temperature, and a maximum decrease of 33% in annual stream flow with 4degree C increase in temperature and 10% decrease in rainfall. Rainfall changes had a greater effect on seasonal as well as annual changes in stream flow than the changes in temperature.